Still waters - Hoag, Tami (New York Bantam Books, 1999)
Newspaper woman Elizabeth Stuart tries to overlook the snobby attitude of the citizens of Still Creek, but circumstances take a turn for the worse when she becomes a murder suspect.
Originally published: New York : Bantam, 1992.
74925
Keywords: Reporters and reporting -- Fiction; Minnesota -- Fiction; Romantic suspense novels; Love stories